Effect of Acrylamide And Potassium Peroxodisulphate on The Quality of Bead Gel Based on Cassava Bagasse-Carrageenan Using Microwave Grafting Method - Distantina, Sperisa; Hidayatun, Nurul; Nabila, Shifa Annisa; Kaavessina, Mujtahid; Fadilah, Fadilah (Program studi Teknik Kimia UNS, 2022)
ABSTRACT. Hydrogels are widely used for drug delivery systems, immuno-chemotherapy applications, efficient use of water, preventing dry soil, and increasing soil infiltration. Generally, hydrogels are derived from synthetic polymers which is non-biodegradable and toxic. Cassava bagasse is an alternative cellulose to make hydrogels. The purpose of this research was to determine the effect of the amount of acrylamide and potassium peroxodisulphate (KPS) initiator on the quality of bead gel based on cassava bagasse-carrageenan. Chemical structure of the hydrogel was studied using FTIR spectroscopy. Cassava bagasse was immersed in a solution of n-hexane to separate the fat. Then, fat-free cassava bagasse was grafted with mass ratios of cassava and acrylamide 1:5, 1:10, and 1:15 in 110 mL water. The solution was added with a KPS initiator with weight variations (g) 0.04; 0.08; 0.12 then stirred 15 min. The solution was put in the microwave with 630 watts of irradiation for 450 s with the cooling cycle temperature maintained at 65-70oC. The aqueous of grafted polymer and carrageenan was injected into beaker glass that contained 1 cm of palm oil and mixture of 0.2 M CaCl2 and 0.2 M KCl in an ice bath. Results showed that the highest average swelling capacity was found in the bead gel variation 1:15 with the number of initiators 0.04 g of 1797.95% at a time of 210 minutes of immersion. From FTIR spectrum, it was found that there was a success in grafting acrylamide into bagasse’s backbone using the microwave grafting method with KPS as initiator.Keywords: Acrylamide, Bead Gel, Cassava Bagasse, Grafting Microwave, Potassium Peroxodisulphate